Digital Access Brokers: Clustering and Comparison (Part I – Locator Services) - Bijan Kumar Roy; Parthasarathi Mukhopadhyay (Journal of Information and Knowledge, 2022)
Scholarly resources published on different platforms are not often searchable and accessible to potential scholars. Google, like other search engines, does not always retrieve free articles on a consistent basis. As a result, there is a gap between the availability and discoverability of scholarly resources. Digital Access Brokers are ground-breaking developments in this context that assemble, discover, and link to open access copies of paid articles or paywalled papers legally uploaded by authors or author-posted manuscripts, with permission from publishers. Browser extensions have emerged as an alternative retrieval assistant to help scholars locate and provide free full-text access to such content available on different publisher sites, databases, open-access journals, or institutional repositories. Unlike other search engines, these extensions provide additional value-added services (such as recommending related resources, citation information, status, type of open access license, level of access and availability of copies by indicating different colours, integration with citation management tools, article metrics) along with the paper to reduce the information overload of the readers. The objective of this paper is to provide an idea about different browser extensions such as Kopernio, Open Access Button, Unpaywall, and along with their key features that might help them in selecting the best tool for their research work.